The Influence of Services’ Quality on Intention to Revisit through Mediation of Satisfaction of Visitors at Sasak Sade Village, Central Lombok, West Nusa Tenggara - Rahman, Rahman; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 6 Number 2 (September 2019), 2019)
The Sasak Sade Village is inhabited by a people from generation to generation. As a place that has been known and visited by many tourists, the management of the Sasak Sade Village offers traditional building house and daily activities of local people as tourist attractions. It is very important to have good quality services to increase revisit intention in the future. The purposes of this research were to determine service quality that influences tourist satisfactions and revisit intention in Sasak Sade Village. This study used 85 respondents of domestic tourists and a purposive sampling technique. The analysis used in this study was a structural equation modeling (SEM) by using Smart Partial Least Square (PLS) 3.0. This study tested two models namely outer model to predict the relationship between indicator and variable, and inner model to predict between two variables.  The results of this research were: 1) the service quality significantly influenced the tourist satisfaction at the Sasak Sade Village; 2) the tourist satisfaction significantly influenced their revisit intention at the Sasak Sade Village; and 3) the service quality significantly influenced  their revisit intention at the Sasak Sade Village. Keywords: Service Quality, Tourist Satisfaction, Revisit Intention